Serum Prolactine Levels and Prolactine Receptor Expression in Premenopausal Breast Cancer: A Potential Predictive Biomarker? - Effif Syofra Tripriadi; Sinta Chaira Maulanisa; Nur Indrawati Lipoeto; Yanwirasti Yanwirasti; Fadil Oenzil; Wirsma Arif Harahap; Tania Nugrah Utami; Farah Mardhiyah (Jurnal Ners, 2026)
Introduction: Premenopausal breast cancer (PBC) is often more aggressive than postmenopausal cases, with prolactin playing a key role in tumor development. This study examines the relationship between serum prolactin levels, prolactin receptor (PRLR) expression, and clinicopathological features in PBC patients. Methods: This cross-sectional study was conducted from 2021 - 2022 at multiple hospitals in Pekanbaru, Indonesia. Thirty-five PBC patients and 35 healthy controls were included. Serum prolactin levels were measured using ELISA, and PRLR expression was assessed via IHC. Statistical analysis was performed using independent t-tests and correlation analysis (p < 0.05). Results: PBC patients had higher prolactin levels (51.96±80.40 ng/mL) than controls (20.83±15.74 ng/mL, p = 0.031). PRLR expression was detected in over 90% of tumors, with a significant correlation between prolactin levels and cancer stage (p = 0.035). Discussion: These findings suggest prolactin contributes to PBC progression, with higher levels linked to advanced stages, possibly through JAK2/STAT5 signaling. Conclusion: Serum prolactin levels and PRLR expression are associated with cancer stage, supporting their potential as biomarkers for early detection and disease progression. Further studies are needed for validation.